Dari Sakral Ke Profan: Pergeseran Budaya Perceraian di Kabupaten Cilacap - Khusnul Khotimah; Maghfur Ahmad (UIN K.H. Abdurrahman Wahid Pekalongan, 2019)
This study discusses whether there is a change in the meaning and nature of marriage, how is the impact of changes in the socio-cultural community of Cilacap so that divorce continues to increase, what factors are the cause of divorce. The concept used by using social construction theories is a continuation of Emile Durkheim's phenomenological theory. This study uses an interdisciplinary qualitative approach in 8 subdistrict cities Cilacap. Data collection techniques used ethnographic study observations and interviews with 36 informants. The findings of socio-cultural changes have resulted in changes in the meaning of marriage which was originally understood to have sacred and sacred meanings to realize a family that is sakinah, mawaddah, and rahmah, changing as ordinary contract that has lost its misfortune. As a result divorce is a normal and natural action without considering the consequences and effects caused. Factors that influence are family economic conditions, hedonic behavior, communication tools, television shows. marriage age, association, infidelity, forced marriage, lack of religious knowledge and low education. The reason for divorce in general is economic factors, namely the inability of husbands to fulfill household needs.